Pelatihan Kerajinan Batik Dalam Rangka Mewujudkan Kampung Batik sebagai Ikon Khas Kelurahan Pakal - Tegar Zakaria Nugraha; Gideon Setyo Budiwitjaksono; Ilvia Azhari Salsabila; Arie Dwi Riskiyanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The majority of housewives in the Pakal sub-district work as housewives whose skills are not honed. In addition to the lack of assistance and training they have received, their capacity and abilities related to creativity management are also limited. This indirectly affects household economic income which is less than optimal. Through one of the work programs of the East Java KKNT-MBKM UPN